2015
DOI: 10.1111/jth.13130
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation indices in very preterm infants from cord blood and postnatal samples

Abstract: Summary. Background: Very premature infants are at high risk of bleeding complications; however, few data exist on ranges for standard coagulation tests. Objectives: The primary objective of this study was to measure standard plasma coagulation tests and thrombin generation in very premature infants compared with term infants. The secondary objective was to evaluate whether an association existed between coagulation indices and intraventricular hemorrhage (IVH). Patients/Methods: Cord and peripheral blood of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 31 publications
6
53
1
1
Order By: Relevance
“…Another study suggested that median aPTT and FBG of cord blood in premature infants were 78.7 seconds and 114 mg/dL, respectively. 10 The median aPTT and FBG in preterm infants were 69.8 seconds and 118 mg/dL, respec-tively, in this study. In our study, we collected the sample after vitamin K2 administration.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Another study suggested that median aPTT and FBG of cord blood in premature infants were 78.7 seconds and 114 mg/dL, respectively. 10 The median aPTT and FBG in preterm infants were 69.8 seconds and 118 mg/dL, respec-tively, in this study. In our study, we collected the sample after vitamin K2 administration.…”
Section: Discussionsupporting
confidence: 44%
“…Other studies of small sample size have reported values of coagulation factors in preterm neonates. 6,10,13 This study demonstrated that various prenatal factors affected coagulation factors. PT-INR was associated with IVH, PA, and Apgar score at 5 minutes, whereas aPTT was associated with BW, GA, and PA.…”
Section: Discussionmentioning
confidence: 66%
“…7 Premature neonatal hemostasis is generally characterized by reduced amounts of vitamin K dependent coagulation factors as well as natural anticoagulants, and secondary hemostasis is therefore considered balanced. 8,9 However, derangements in activated partial thromboplastin time (APTT), international normalized ratio (INR), and prothrombin time (PT) have been associated with IVH in premature neonates. 10,11 While thrombocytopenia is common in premature neonates, 12 controversies exist on the role of platelet counts in IVH among the premature neonates.…”
mentioning
confidence: 99%
“…Plasma levels of thrombin-antithrombin complexes, D-dimer, fibrinogen, and fibrin degradation products are higher in infants with birth asphyxia [69]. It should be noted that levels of coagulation factors II, VII, IX, and X, protein C, protein S and antithrombin are also reduced in preterm compared with term plasma [70]. Prothrombin time (PT) and activated partial thromboplastin time (aPTT) are higher in preterm infants, but there is no correlation with increased risk of intraventricular hemorrhage (IVH) with higher coagulation times [70].…”
Section: Liver Injury Coagulopathy and Bleedingmentioning
confidence: 99%